"I'm Going to Learn, and She's Going to Become Somebody": Exploring the Counternarratives of Black Women on Welfare in Urban Communities. (April 2022) - Moran, Kaitlin K.
This qualitative research study explores counternarratives to stereotypes and assumptions made about Black women on welfare in low-income, urban communities. Findings, based on in-depth interviews with 33 mothers and grandmothers, challenge perceptions of "welfare queens"—breeders of children, absorbed by the culture of poverty, and disinterested in their children's education. Participants defy stereotypes by raising children in well-supported family structures while gainfully employed, pursuing educational opportunities, or a combination of the two. The women actively contribute to their communities' culture of wealth by investing in their children. The paper concludes with recommendations and directions for future research.